Fraud and Digital Crime: Challenges and Solutions in the Era of Blockchain Technology - Sahwa Mointi, Nurul Ananda (Universitas Negeri Gorontalo, 2025)
This study aims to identify the challenges in combating fraud crimes involving blockchain technology and explore effective solutions to address these issues. The research uses a descriptive qualitative approach with a case study. Data is collected through a literature review of relevant literature on blockchain, digital fraud, as well as regulations and policies implemented in various countries. The findings of this study reveal several key challenges in addressing fraud crimes involving blockchain. First, the anonymous nature of blockchain transactions makes it difficult to track and identify fraudsters. Second, the decentralized nature of blockchain reduces the role of central authorities in overseeing and controlling transactions. Third, the lack of clear regulations in several countries regarding the use of blockchain and cryptocurrency. Proposed solutions include the use of analytical technology, such as blockchain forensics, to track transaction traces, as well as strengthening regulations on cryptocurrency, including identity verification and reporting suspicious transactions. Additionally, education and digital literacy for the public are essential to raise awareness about digital fraud risks and provide a better understanding of how to protect oneself in the blockchain world